Information system for monitoring supervision and reporting the performance of religious subject teachers - Zainuri, Ahmad; Fakhriza, Muhammad (Jurnal Info Sains : Informatika dan Sains, 2024)
The rapid development of technology requires that every individual, company and government agency, including educational institutions, must keep abreast of developments. The Ministry of Religion of South Labuhanbatu Regency, the government agency that oversees religious subject teachers, plays an active role in supervising the performance of religious subject teachers so that they are able to carry out their duties properly. The current monitoring system still uses a makeshift archive system. One solution to this problem is the support of a website-based information system using the divide and conquer algorithm to make it easier to manage real data into a website system. This system is designed using PHP and a database server used by MySQL. The end result of the research is to produce a website-based system that can help monitor teacher data collection at the Ministry of Religion of Labuhan Batu Selatan Regency, and make it easier for teachers to report the performance of religious subject teachers